Which measure of drop jump performance best predicts sprinting speed? - Barr, M. J.; Nolte, V. W. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to evaluate which measure of a drop jump (DJ) has the highest correlation with sprinting speed over 60 m. For use of comparison, maximal leg strengths in a front squat, countermovement jump, and squat jump were also assessed. The subjects in the study were all high-caliber female university rugby players. Subjects did DJs from 0.12, 0.24, 0.36, 0.48, 0.60, 0.72, and 0.84 m. Jump height and reactive strength index (RSI) were calculated at each drop height. Pearson correlations were used to analyze the relationship between the strength and jumping measures with sprinting speed. The DJ height from 0.84 m had the highest negative correlation with 0- to 10-m split (r = -0.66), the 10- to 30-m split (r = -0.86) and 30- to 60-m split (r = -0.86). The use of RSI is questioned as a measurement of DJ performance. It is suggested that maximal height achieved in a DJ is the most important DJ measure. If it is desired to measure ground contact time, then it may be more useful to use a second test where the jump height for the athlete is set by having the athlete jump onto a box or touch a target overhead set at a standard height and measure the ground contact time with a switch mat or force plate.